Coronatine Inhibits Stomatal Closure through Guard Cell-Specific Inhibition of NADPH Oxidase-Dependent ROS Production - Toum, Laila; Torres, Pablo S.; Gallego, Susana M.; Benavídes, María P.; Vojnov, Adrián A.; Gudesblat, Gustavo E. (Frontiers in Plant Science, 2016)
Microbes trigger stomatal closure through microbe-associated molecular patterns (MAMPs). The bacterial pathogen Pseudomonas syringae pv. tomato (Pst) synthesizes the polyketide toxin coronatine, which inhibits stomatal closure by MAMPs and the hormone abscisic acid (ABA). The mechanism by which coronatine, a jasmonic acid-isoleucine analog, achieves this effect is not completely clear. Reactive oxygen species (ROS) are essential second messengers in stomatal immunity, therefore we investigated the possible effect of coronatine on their production. We found that coronatine inhibits NADPH oxidase-dependent ROS production induced by ABA, and by the flagellin-derived peptide flg22. This toxin also inhibited NADPH oxidase-dependent stomatal closure induced by darkness, however it failed to prevent stomatal closure by exogenously applied H2O2 or by salicylic acid, which induces ROS production through peroxidases. Contrary to what was observed on stomata, coronatine did not affect the oxidative burst induced by flg22 in leaf discs. Additionally, we observed that in NADPH oxidase mutants atrbohd and atrbohd/f, as well as in guard cell ABA responsive but flg22 insensitive mutants mpk3, mpk6, npr1-3 and lecrk-VI.2-1, the inhibition of ABA stomatal responses by both coronatine and the NADPH oxidase inhibitor diphenylene iodonium was markedly reduced. Interestingly, coronatine still impaired ABA-induced ROS synthesis in mpk3, mpk6, npr1-3 and lecrk-VI.2-1, suggesting a possible feedback regulation of ROS on other guard cell ABA signalling elements in these mutants. Altogether our results show that inhibition of NADPH oxidase-dependent ROS synthesis in guard cells plays an important role during endophytic colonization by Pst through stomata.